2021
DOI: 10.1016/j.cell.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of TNF-α and IFN-γ Triggers Inflammatory Cell Death, Tissue Damage, and Mortality in SARS-CoV-2 Infection and Cytokine Shock Syndromes

Abstract: Highlights d Of several cytokines tested, only synergism of TNF-a and IFN-g induces PANoptosis d TNF-a and IFN-g-mediated PANoptosis perpetuates cytokine storm d TNF-a and IFN-g shock mirrors cytokine storm syndromes, including COVID-19 d Neutralizing TNF-a and IFN-g protects against SARS-CoV-2, HLH, and sepsis in mice

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
917
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,200 publications
(1,085 citation statements)
references
References 133 publications
31
917
3
5
Order By: Relevance
“…The cytokine release syndrome (CRS) or cytokine storm is a major cause of acute lung damage associated with patient mortality [38][39][40][41][42][43] . Because the cytokine storm is also common in sepsis caused by other pathogens 42,44 , we determined the mRNA levels of key proinflammatory cytokines and chemokines in the PBMCs of the COV (D1) and ICU cohorts in comparison to the heathy controls.…”
Section: Excessive Jak-stat Signaling Associated With the Cytokine Stormmentioning
confidence: 99%
“…The cytokine release syndrome (CRS) or cytokine storm is a major cause of acute lung damage associated with patient mortality [38][39][40][41][42][43] . Because the cytokine storm is also common in sepsis caused by other pathogens 42,44 , we determined the mRNA levels of key proinflammatory cytokines and chemokines in the PBMCs of the COV (D1) and ICU cohorts in comparison to the heathy controls.…”
Section: Excessive Jak-stat Signaling Associated With the Cytokine Stormmentioning
confidence: 99%
“…While we await understanding of the chief cytokine culprits of severe COVID-19, it might be that broad targeting is more fruitful; murine studies suggest the potential of greater effects of dual cytokine blockade than those of blocking individual cytokines. 9 This is further supported by the evidence, albeit limited, that JAK kinase inhibitors such as baricitinib, which also have a mechanism encompassing blockade of multiple cytokines, can be beneficial for the treatment of COVID-19.…”
mentioning
confidence: 95%
“…In conclusion, we identified a novel mechanism of cell signaling integration controlling the transcriptional and proliferative response of regulatory T cells. While this is demonstrated in T cells using only two cytokines, these findings indicate that combinatorial signaling with other cytokines and cell types is possible, and is even beginning to emerge in the literature ( Karki et al, 2021 ). Moreover, while these differences in response may underlie cytokine pleiotropy, they also provide an intriguing guide for new therapeutic applications of combinatorial cytokines in the clinical setting ranging from ex vivo support of autologous cell transfers to immune activation in cancer and inhibition for autoimmunity.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the global COVID-19 pandemic has brought attention to the devastating effects of cytokine storms, with one study finding that TNFα and IFNγ synergize to trigger inflammatory cell death and increased mortality in SARS-CoV-2 infection ( Karki et al, 2021 ). Mechanistically, previous studies have shown that two cytokines can cooperate by sharing the same STAT proteins to either enhance or interfere with the other to form a different outcome ( Lin and Leonard, 2019 ; Johnston et al, 2012 ; Liao et al, 2011 ), thereby demonstrating the importance of understanding how cytokines may influence each other.…”
Section: Discussionmentioning
confidence: 99%